Penyuluhan Pendewasaan Usia Perkawinan Anak Bagi Masyarakat di Kecamatan Kunduran Kabupaten Blora - Era Kurniati (Pusat Riset dan Inovasi Nasional, 2023)
Counseling about maturing the age of marriage is a means of communication, information and discussion of problems that exist in an area. Counseling on the maturity of child marriage aims to increase knowledge & awareness in making decisions regarding marriages that are healthy, safe and in accordance with the laws and regulations in force in our country. Besides that, counseling on child marriage maturity is a strategy in order to improve the health status of mothers and babies so that there are no cases of high-risk pregnant women due to child marriage, marriage at a young age is very vulnerable to hypertension in pregnancy, abortion and babies born with LBW or stunting. Counseling on the maturation of child marriage was given to families who have children who are still in junior high school - high school, health cadres & village officials totaling 150 people from 5 village locations in the Kunduran District area. After being given counseling, it is hoped that all participants and officials will have a commitment to try to reduce cases of child marriage in their respective village areas.